The legacy of the Siege of Leningrad, 1941-1995 : myth, memories, and monuments - Kirschenbaum, Lisa A. (Cambridge University Press, 2006)
The World War II siege of Leningrad constituted one of the most dramatic and tragic episodes of the war. Since 1941, the remarkable story of the blockade has been retold in countless memoirs, interviews, diaries, histories, films, monuments, poems, and museum exhibits. This book follows these stories.